A light-PKI Fast Authentication Model - Li, D.; Wang, Shaobin; Li, Z. (2011)
A light-PKI Fast Authentication Model is proposed to improve the speed of communications authentication. In the light-PKI model, the root public key, CRL and canceled certificate are stored safely in terminal. It dose not need the TTP when two terminals authenticate each other. So, this model can enhance the authentication speed of PKI systems. © 2011 IEEE.